2018
DOI: 10.1021/jacs.7b12860
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Mixed Guanidinium–Methylammonium Phases with Exceptionally Long Carrier Lifetimes for High-Efficiency Lead Iodide-Based Perovskite Photovoltaics

Abstract: Methylammonium (MA)- and formamidinium (FA)-based organic-inorganic lead halide perovskites provide outstanding performance as photovoltaic materials, due to their versatility of fabrication and their power conversion efficiencies reaching over 22%. The proposition of guanidinium (GUA)-doped perovskite materials generated considerable interest due to their potential to increase carrier lifetimes and open-circuit voltages as compared to pure MAPbI. However, simple size considerations based on the Goldschmidt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
299
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(312 citation statements)
references
References 40 publications
7
299
0
1
Order By: Relevance
“…The photoluminescence (PL) intensity of the optimized DMA doped film is ≈2× higher than that of MA1. [23] This is consistent with the higher formation energy of the perovskite structure obtained in DFT studies. The longer PL lifetime along with the higher steady-state PL of DMA0.11 indicates that the nonradiative recombination is reduced in the DMA-incorporating films, suggesting that the trap state density is reduced.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscomsupporting
confidence: 87%
“…The photoluminescence (PL) intensity of the optimized DMA doped film is ≈2× higher than that of MA1. [23] This is consistent with the higher formation energy of the perovskite structure obtained in DFT studies. The longer PL lifetime along with the higher steady-state PL of DMA0.11 indicates that the nonradiative recombination is reduced in the DMA-incorporating films, suggesting that the trap state density is reduced.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscomsupporting
confidence: 87%
“…We have previously shown that bulk mechanochemical perovskites are indistinguishable from those prepared using solution processing only when pure phases are formed. [29] Since there is no clear evidence for the presence of δ-FAPbI 3 in the X-ray diffraction patterns of the solutionprocessed films (Figure 3a,b), we conclude that the ratio of α-FAPbI 3 to δ-FAPbI 3 in the presence of spacer A is affected by the solvent, such that the formation of δ-FAPbI 3 is suppressed. [29] Since there is no clear evidence for the presence of δ-FAPbI 3 in the X-ray diffraction patterns of the solutionprocessed films (Figure 3a,b), we conclude that the ratio of α-FAPbI 3 to δ-FAPbI 3 in the presence of spacer A is affected by the solvent, such that the formation of δ-FAPbI 3 is suppressed.…”
Section: Structural Characteristicsmentioning
confidence: 74%
“…We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far. We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…Photogenerated carries had much longer time in the perovskite film prepared from the 2ME‐based and PbAc 2 ‐containg solution as confirmed by TRPL (Figure d), which was responsible for the higher photovoltaic performance. Addition of guanidinium cation (GA) in the (MAI+PbI 2 +PbAc 2 ) solution improved further PCE over 19% due to further improvement in carrier lifetime …”
Section: Scalable Technologiesmentioning
confidence: 99%